Soft skin [videorecording (DVD)] - Truffaut, François; Desailly, Jean; Dorléac, Françoise; Benedetti, Nelly; Ceccaldi, Daniel, 1927-2003 (Criterion collection, 2015)
A celebrated literary scholar, seemingly happily married, embarks on an affair with a gorgeous stewardess, who is captivated by his charm and reputation. As their romance gets serious, the film grows anxious, leading to a wallop of a conclusion.